Layanan Internet Service Provider dengan GNS3 Menggunakan Mikrotik dan Debian pada Jaringan Dual ISP - Amalia Yos Andra; Hanriyawan Adnan Mooduto; Fanni Sukma; Hidra Amnur (SOTVI - Society of Visual Informatics, 2026)
An Internet Service Provider (ISP) is a service that provides internet access to users, and in the digital era, the need for stable, secure, and easy-to-manage connectivity is increasing. This study aims to design and implement a simulation-based ISP service using GNS3 with Mikrotik and Debian devices on a dual ISP network. The focus of the research includes the implementation of the OSPF routing protocol for inter-router connectivity, load balancing and failover configurations to maintain network stability, the implementation of PPPoE and Hotspot as user authentication integrated with the Radius server, and the use of a Discord Bot on a Debian server for real-time network monitoring. The results of the study indicate that the dual ISP system is capable of performing load balancing and failover well, PPPoE and Hotspot services can be used for user authentication, and network monitoring via the Discord Bot runs according to its function. The conclusion of this study shows that a GNS3-based design with Mikrotik and Debian can be an effective simulation solution to support ISP service availability, optimize user management, and improve network monitoring system